‘Spindle of Endeavor’ in the Hands of a Mixed-Breed Spider: Parvin Etesami's Creative Reception of Whitman - Behnam Fomeshi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
In her poetry Pravin Etesami (1907-1941) has freely borrowed from multiple sources, including Aesop's and La Fontaine’s Fables, her father’s translations of foreign literatures, as well as Persian classical poetry. However, the resulting work remained distinctly her own. A number of critical studies have investigated the relationship between Etesami's poem "God's Weaver" and various texts that inspired or influenced it. Such studies argue that the poem “is based” on a translation into Persian of an editorial by Arthur Brisbane. However, the present paper examines “God’s Weaver” in relation to Walt Whitman’s “A Noiseless Patient Spider” to shed light on Etesami's yet unexplored creative reception of Whitman. The paper ends with suggestions on revisiting the relation between tradition and modernity in Persian poetry as well as the relation between Persian poetry and world literature.